RNA Sequencing Reveals that Endoplasmic Reticulum Stress and Disruption of Membrane Integrity Underlie Dimethyl Trisulfide Toxicity against Fusarium oxysporum f. sp. cubense Tropical Race 4 - Zuo, Cunwu; Zhang, Weina; Chen, Zhongjian; Chen, Baihong; Huang, Yonghong (Frontiers in Microbiology, 2017)
Fusarium wilt of banana, a destructive disease that affects banana production, is caused by Fusarium oxysporum f. sp. cubense tropical race 4 (Foc TR4). In a previous study, we confirmed the strong inhibitory effects of Chinese leek (Allium tuberosum) on the incidence of this disease. Sulfur compounds are the primary antifungal constituents of Chinese leek. Among these, dimethyl trisulfide (DT) was the most abundant and exhibited the strongest inhibition of Foc TR4 growth and development. In the present study, the global gene expression profiles of Foc TR4 isolates treated with DT at 4,000 folds dilution (concentration of 1/4,000, v/v) for 1.5, 6, and 12 h were investigated by using RNA sequencing. The expression patterns of 15 DEGs were validated based on quantitative real-time PCR (qRT-PCR) assay. Untreated sample presented 2,556, 1,691, and 1,150 differentially expressed genes (DEGs) at 1.5, 6, and 12 h after the onset of the experiment, respectively, whereas DT-treated isolates presented 2,823, 3,546, and 6,197 DEGs. Based on Gene Ontology annotation and Kyoto Encyclopedia of Genes and Genomes enrichment analysis, DEGs involved in endoplasmic reticulum (ER), glycosylation, and steroid biosynthesis were significantly inhibited by DT exposure. The similar expressional patterns of 15 DEGs between RNA-seq and qRT-PCR assays indicated the reliability of the RNA-seq data. Thus, ER stress related to glycosylation inhibition and damage to cell membrane integrity might contribute to the toxicity of DT against Foc TR4. As the results presented here evidenced changes in gene expression associated with DT exposure, which might be used to develop new approaches for controlling FWB.